From Grammar to Science : New Foundations for General Linguistics. - Yngve, Victor H., 1920-2012 (John Benjamins Pub. Co., 1996)
Although efforts have been under way for the past two centuries to treat language scientifically, linguists and others who work with language, speech, or communication have not found an adequate scientific foundation in current linguistic theory. Many of the difficulties are caused by longstanding confusions between the logical domain of science and grammar and the physical domain of sound waves and the people who speak and understand. In this book, therefore, the last impediments of tradition, the ancient semiotic-grammatical foundations of linguistics, are set aside. We move into the physical.